Financial Literacy, Career Ambitions, and Childfree Decisions among Millennial Couples in Pidie Jaya: A Maqāṣid al-Sharī‘ah Perspective - Muhammad Jafar; Miftahul Jannah (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study examines the phenomenon of childless living among millennial couples in Pidie Jaya Regency, a region characterised by strong Islamic and Acehnese cultural values. The research aims to analyse how financial literacy and career ambitions influence couples’ decisions to remain childless, using Maqāṣid al-Sharī‘ah as a critical analytical framework. Employing a qualitative descriptive method, data were collected through in-depth interviews with ten selected millennial couples. Empirical findings indicate that financial literacy and career aspirations contribute to a risk-mitigation approach to family planning among the informants. Rather than signifying a total paradigm shift in society, this phenomenon reflects micro-level adaptation by specific couples facing the complexities of the modern economy. Analysed through Maqāṣid al-Sharī‘ah, the findings reveal a dynamic tension between the traditional priority of ḥifẓ al-nasl (preservation of lineage) and the couples’ direct focus on ḥifẓ al-māl (protection of property) and ḥifẓ al-nafs (protection of life/mental well-being). This study concludes that the decision not to have children among these particular couples constitutes a renegotiation of individual family planning, driven by financial and psychological readiness. This research contributes to sociological studies of Islamic family law by providing empirical evidence of how traditional theological narratives are critically navigated by the millennial generation in semi-rural societies.